Gender and the sexes in the Indonesian Archipelago - Schouten, Maria Johanna Christina (2017)
Review of collection of studies regarding gender in several regions of Southeast Asia. The articles in this volume, first presented as papers at a conference of the Association for South-East Asian Studies in the United Kingdom, add to the literature on gender in Southeast Asia. Although that literature may seem extensive by now, this publication is certainly not repetitive or redundant. On the contrary, besides presenting awealth of data, it attests to how useful and refreshing an approach which focuses on gender and gender relations can be, even when examining seemingly well-known facts.